The Effect of Leadership, Motivation, and Work Environment on Employee Performance at Hermina Hospital Makassar - Ramli, Muhammad Alamsyah; Mangkona, Suriyanti (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This study aims to determine whether leadership, motivation, and work environment have a positive and significant effect on the performance of Hermina Hospital Makassar employees. In this study, the number of samples studied were 76 people from 300 people from the number of employees of Hermina Hospital Makassar. The results of this study prove that: (1) Leadership has a positive and significant effect on Employee Performance; (2) Motivation has a positive and significant effect on Employee Performance; (3) The Work Environment has a positive and significant effect on Employee Performance.